Fundamentals of materials science and engineering - Callister, William D., 1940- (Wiley, 2013)
Callister and Rethwisch's Fundamentals of Materials Science and Engineering, 4th Edition continues to take the integrated approach to the organization of topics. That is, one specific structure, characteristic, or property type at a time is discussed for all three basic material types -- metals, ceramics, and polymeric materials. This order of presentation allows for the early introduction of non-metals and supports the engineer's role in choosing materials based upon their characteristics. Also discussed are new, cutting-edge materials. Using clear, concise terminology that is familiar to students, Fundamentals presents material at an appropriate level for both student comprehension and instructors who may not have a materials background.